102k views
0 votes
Simplify using exponent rules. 2^4x4^6/2^-3x4^4​

User Shakaron
by
4.7k points

1 Answer

1 vote


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] ~\dotfill\\\\ \cfrac{2^4* 4^6}{2^(-3)* 4^4}\implies 2^4\cdot 2^3\cdot 4^6\cdot 4^(-4)\implies 2^(4+3)\cdot 4^(6-4)\implies 2^7\cdot 4^2\implies 2^7\cdot (2^2)^2 \\\\\\ 2^7\cdot 2^(2\cdot 2)\implies 2^7\cdot 2^4\implies 2^(7+4)\implies 2^(11)\implies 2048

User Burak SARICA
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.